The Simple Keynesian Theory • Some Basic Definitions – Endogenous variables The Simple Keynesian Theory of Income Determination • Output • Consumer Spending – To become endogenous variables • Investment spending • Net exports • Interest rates • Inflation September 7 & 9, 1999 1 September 7 & 9, 1999 2 The Simple Keynesian Theory The Simple Keynesian Theory • Some Basic Definitions (continued) • Some Basic Definitions (continued) – Exogenous variables – Exogenous variables (continued) • Policy instruments • Demand shocks – Money supply – Government spending – Tax rates September 7 & 9, 1999 – Unpredictable changes in » Consumer spending » Investment spending » Net exports † Foreign economic activity – Abrupt changes in technology – Changes in regulations – Wars – Political crises 3 September 7 & 9, 1999 4 The Simple Keynesian Theory The Simple Keynesian Theory • Some Basic Definitions (continued) • Determining Equilibrium Income – Exogenous variables (continued) – By definition • Supply shocks E = C + I + G + NX – Large changes in oil prices – Large changes in raw material prices » Agricultural » Industrial – Now assume • C, G and NX are always equal to planned • Only I can differ from planned I = I(p) + I(u) • Parameters • Therefore E(p) = C + I(p) + G + NX September 7 & 9, 1999 5 September 7 & 9, 1999 6 1 Figure 3-1 A Simple Hypothesis Regarding Consumption Behavior The Simple Keynesian Theory • Determining Equilibrium Income (con’t) – The Consumption Function • Autonomous consumption • Induced consumption – marginal propensity to consume • General linear form C=a+c(Y-T) » Figure 3-1 September 7 & 9, 1999 7 September 7 & 9, 1999 8 Figure 3-3 Consumption, Saving, and Disposable Income, 1929–96 The Simple Keynesian Theory • Determining Equilibrium Income (con’t) – The Savings Function • Autonomous saving » Figure 3-3 • Induced saving – marginal propensity to save • General linear form S=(Y-T)-C =(Y-T)-a-c(Y-T) = -a + (1 - c) ( Y - T) = -a + s ( Y - T ) September 7 & 9, 1999 9 September 7 & 9, 1999 10 Figure 3-2 The Relation Between Induced Consumption, Induced Saving, and the Consumption Function The Simple Keynesian Theory • Determining Equilibrium Income (con’t) – Consumption & Savings (Figure 3-2) (Y-T)=C+S = a + c ( Y - T ) -a + s ( Y - T ) =(c+s)(Y-T) (c+s)=(Y-T)/(Y-T) =1 so c + s = 1 ; c = 1 - s ; s = 1 - c September 7 & 9, 1999 11 September 7 & 9, 1999 12 2 Figure 3-4 Autonomous Planned Spending and the Level of Total Planned Expenditure The Simple Keynesian Theory • Determining Equilibrium Income (con’t) – Equilibrium • Equilibrium is a situation in which there is no pressure for change • Total Planned Expenditures E(p) = C + I(p) + G + NX = a + c ( Y - T ) + I(p) + G + NX = a + cY - cT + I(p) + G + NX » Figure 3-4 September 7 & 9, 1999 13 September 7 & 9, 1999 14 The Simple Keynesian Theory The Simple Keynesian Theory • Determining Equilibrium Income (con’t) • Determining Equilibrium Income (con’t) – Equilibrium (continued) – Equilibrium (continued) • It is always true that Y=E Y = E(p) + I(u) • Autonomous Planned Spending A(p) = a - cT + I(p) + G + NX – where I(u) is unintended inventory investment • Total Planned Expenditures • Equilibrium exists only when E(p) = A(p) + cY September 7 & 9, 1999 Y = E(p) 15 September 7 & 9, 1999 or I(u) = 0 16 Figure 3-5 How Equilibrium Income is Determined The Simple Keynesian Theory • Determining Equilibrium Income (con’t) – Disequilibrium Dynamics (continued) • Example » Figure 3-5 • Does I(u) need to be reversed? September 7 & 9, 1999 17 September 7 & 9, 1999 18 3 The Simple Keynesian Theory The Simple Keynesian Theory • Determining Equilibrium Income (con’t) • Determining Equilibrium Income (con’t) – Equilibrium (continued) – Equilibrium (continued) • Autonomous planned spending equals induced saving in equilibrium • Autonomous planned spending equals induced saving in equilibrium (continued) Y = E(p) Y - cY = E(p) - cY ( 1 - c ) Y = A(p) sY = A(p) – Induced saving = autonomous spending – Leakages = injections – remember s=1-c September 7 & 9, 1999 Y(e) = A(p) / s 19 September 7 & 9, 1999 20 The Simple Keynesian Theory The Simple Keynesian Theory • The Multiplier Effect • The Multiplier (continued) k = Change in Y / Change in A(p) – An example • from – Calculating the Multiplier Change in Y = Change in A(p) / s • How much does income change? Y(1) = A(p)(1) / s Y(0) = A(p)(0) / s Change in Y = Change in A(p) / s k = Change in A(p) / s / Change in A(p) k=1/s • Relationship between leakages and the multiplier? » Figure 3-6 September 7 & 9, 1999 21 Figure 3-6 The Change in Equilibrium Income Caused by a $250 Billion Increase in Autonomous Planned Spending September 7 & 9, 1999 22 The Simple Keynesian Theory • Fiscal Policy – Fiscal Policy Definitions • Changes in government spending • Changes in autonomous tax revenues • Changes in tax rates – Now A(p) = a - cT + I(p) + G + NX September 7 & 9, 1999 23 September 7 & 9, 1999 24 4 The Simple Keynesian Theory The Simple Keynesian Theory • Government Spending Multiplier • Government Spending Multiplier (con’t) – If – The Government Budget Deficit Change in Y = Change in A(p) / s ( G - T ) = S - I - NX Change in G - Change in T = Change in S - Change in I - Change in NX – then Change in A(p) = Change in G Change in Y = Change in G / s k = Change in G / s / Change in G =1/s September 7 & 9, 1999 • but Changes in T, I, and NX = 0 • therefore, 25 September 7 & 9, 1999 26 The Simple Keynesian Theory The Simple Keynesian Theory • Government Spending Multiplier (con’t) • The Tax Multiplier – The Government Budget Deficit (continued) – Autonomous Taxes Change in G = Change in S Change in A(p) = -c ( Change in T ) • or Change in G = s ( change in Y) September 7 & 9, 1999 27 September 7 & 9, 1999 28 The Simple Keynesian Theory The Simple Keynesian Theory • The Tax Multiplier (continued) • Balanced Budget Multiplier k(G) = 1 / s & k(T) = -c / s – Autonomous Tax Multiplier k(T) = Change in Y / Change in T – therefore, • Remember k(G) + k(T) = [ 1 / s ] + [ -c / s] =[1-c]/s =s/s =1 Change in Y = Change in A(p) / s = [-c ( Change in T )] / s • therefore k(T) = -c ( Change in T ) / s ( Change in T ) = -c / s September 7 & 9, 1999 » Figure 3-7 29 September 7 & 9, 1999 30 5 Figure 3-7 Effect on Income of a $250 Billion Increase in Government Spending Followed by a $250 Billion Increase in Autonomous Tax Revenue The Simple Keynesian Theory • The Tax Multiplier (continued) – Effect of Income Taxes • Autonomous taxes • Induced taxes • General linear form • Now September 7 & 9, 1999 31 T = T(a) + tY YD = Y - T = Y - T(a) - tY = ( 1 - t ) Y - T(a) September 7 & 9, 1999 32 The Simple Keynesian Theory The Simple Keynesian Theory • The Tax Multiplier (continued) • The Tax Multiplier (continued) – Effect of Income Taxes (continued) – Effect of Income Taxes (continued) • Induced consumption • Induced saving C=a+c(Y-T) = a + c ( Y - T(a) - tY ) =a+c(1-t)Y September 7 & 9, 1999 S=(Y-T)-C = Y - T(a) - tY -a - c ( 1 - t ) Y = -a + ( 1 - t ) Y - c ( 1 - t ) Y = -a + ( 1 - c ) ( 1 - t ) Y = -a + s ( 1 - t ) Y 33 September 7 & 9, 1999 34 The Simple Keynesian Theory The Simple Keynesian Theory • The Tax Multiplier (continued) • The Tax Multiplier (continued) – Effect of Income Taxes (continued) – Effect of Income Taxes (continued) • Induced income tax revenues • Total induced changes T = T(a) + tY c(1-t)+s(1-t)+t (c+s)(1-t)+t (1 - t ) + t 1 September 7 & 9, 1999 35 September 7 & 9, 1999 36 6 The Simple Keynesian Theory The Simple Keynesian Theory • The Tax Multiplier (continued) • The Tax Multiplier (continued) – Equilibrium Income with Income Taxes – Income Taxes and the Multiplier Change in Y = Change in A(p) / [ s ( 1 - t ) + t ] Y = E(p) Y - c ( 1 - t ) Y = E(p) - c ( 1 - t ) Y [ 1 - c ( 1 - t ) ] Y = A(p) • so k=1/[s(1-t)+t] • or • so = 1/ marginal leakage rate Y(e) = A(p) / [ 1 - c ( 1 - t ) ] = A(p) / [ s ( 1 - t ) + t ] September 7 & 9, 1999 37 September 7 & 9, 1999 38 The Simple Keynesian Theory The Simple Keynesian Theory • The Tax Multiplier (continued) • The Tax Multiplier (continued) – Income Taxes, the Multiplier and Stabilization Policy – Income Taxes and the Gov’t Budget Deficit • Income taxes reduce the size of the multiplier G - T = G - T(a) - tY – A smaller multiplier means business cycles are dampened – Income taxes are an automatic stabilizer. • Y(e) changes when tax rates change • Induced taxes makes the deficit cyclical – Y(e) increases when tax rates are reduced – Y(e) decreases when tax rates are increased September 7 & 9, 1999 – actual deficit – structural deficit 39 September 7 & 9, 1999 The Simple Keynesian Theory The Simple Keynesian Theory • The International Trade Multiplier • The International Trade Multiplier – Autonomous net exports 40 – The multiplier now becomes • exports • autonomous imports k = 1 / [ s ( 1- t ) + t + nx ] – Induced net exports • imports – The multiplier becomes smaller the larger is the economy’s elasticity to import. – General linear form NX = NX(a) - nxY September 7 & 9, 1999 41 September 7 & 9, 1999 42 7 The Simple Keynesian Theory • Summarizing the Multiplier k = 1 / marginal leakage rate Types of leakages Saving only Saving and income tax Saving, income tax, and imports Marginal leakage rate s s(1-t)+t s ( 1 - t ) + t + nx – Implications for business cycles – Implications for stabilization policy September 7 & 9, 1999 43 8